Glycated Hemoglobin and Risk of Arterial Stiffness in a Chinese Han Population: A Longitudinal Study - Han, Ze; Kang, Xiaoping; Zhang, Jie; Wang, Jinqi; Liu, Yue; Liu, Jia; Wu, Zhiyuan; Li, Xia; Zhao, Xiaoyu; Guo, Xiuhua; Chen, Shuo; Tao, Lixin (Frontiers in Endocrinology, 2022)
Background and aims Glycated hemoglobin (HbA1c) associates with the risk of arterial stiffness, and such association can be found between fasting blood glucose (FBG), postprandial blood glucose (PBG), triglyceride-glucose index (TyG index) and arterial stiffness. But the results were inconsistent, longitudinal studies were sparse, and comparison of these glycemic parameters was less conducted. We aimed to explore the longitudinal relationship between HbA1c and arterial stiffness and compare the effect of the parameters. Methods Data were collected from 2011-2019 in Beijing Health Management Cohort (BHMC) study. Cox proportional hazard models were fitted to investigate the association between the parameters and arterial stiffness. Generalized estimation equation (GEE) analysis was conducted to investigate the effect of repeated measurements of glycemic parameters. Receiver operating characteristic (ROC) analysis was performed to compare the predictive value of glycemic parameters for arterial stiffness. Results Among 3048 subjects, 591 were diagnosed as arterial stiffness during the follow-up. The adjusted hazard ratio (HR) (95% confidence interval (CI)) for arterial stiffness of the highest quartile group of HbA1c was 1.63 (1.22-2.18), which was higher than those of FBG, PBG and TyG index. The nonlinear association of arterial stiffness with HbA1c and PBG was proved. And the robust results of sensitivity analysis were obtained. Conclusions HbA1c is an important risk factor of arterial stiffness compared with PBG, FBG and TyG index, and has a strong predictive ability for arterial stiffness among non-diabetics and the general population.